The impact of green HRM practices on green innovative work behaviour: empirical evidence from the hospitality sector of China and Pakistan - Karamat Khan; Eimad Hafeez Gogia; Zhen Shao; Mohd Ziaur Rehman; Assad Ullah (BMC Psychology)
Abstract Amid a global shift towards eco-friendly practices, this study investigates the impact of green human resource management (GHRM) practices on green innovative work behavior (GIWB) in the hospitality sector, focusing on emerging and developing countries, specifically China and Pakistan. The research also explores the mediating roles of green perceived organizational support (GPOS) and organizational citizenship behavior towards the environment (OCBE), as well as the moderating role of green transformational leadership (GTL). This study is grounded in the AMO (ability, motivation, and opportunity) theory and organizational support theory. Data were collected through a questionnaire, yielding 503 valid responses from hotel employees in Beijing, China, and 498 valid responses from Islamabad, Pakistan. Structural Equation Modeling (SEM) was employed to examine and compare the results across both samples. The findings reveal positive and significant relationships between GHRM and GIWB, as well as notable mediation and moderation effects among the specified variables. Interestingly, GTL did not significantly moderate the relationship between GHRM and GIWB in Pakistan’s sample, highlighting a regional contrast. This study contributes to advancing the implementation of GHRM practices to enhance GIWB in the hospitality sector, with insights into the role of GTL across different cultural contexts.